The Influence of Workload and Work Discipline on Employee Performance in Companies in Bekasi City - Pramukty, Rachmat; Dewi Puspaningtyas Faeni (Green Publisher, 2022)
This study aims to determine the effect of workload and work discipline on employee performance at companies in Bekasi City. The population in this study were employees with a population of 57 respondents and the sample taken in this study were employees with a population of 43 people. The sampling technique was carried out using a simple random sampling technique which means that each element of the population has the same opportunity to be sampled. This research uses quantitative methods, where the data collection methods used are observation, questionnaires, and documentation. The data quality test uses validity, and reliability tests. Classical assumption test using normality, multicollinearity and heteroscedasticity tests. The analysis method used is multiple linear regression analysis and t test (partial test). The results showed that the Workload variable had a significant effect on employee performance at companies in Bekasi City, while Work Discipline had a significant effect on employee performance. This is shown from the calculation results, namely workload has an effect of 0.332 and work discipline has an effect of 0.639 on employee performance.